Osteoporosis in Patients with Ankylosing Spondylitis - Review - Yasemin Dinçer Turan; Mehmet Tuncay Duruöz (Galenos Yayinevi, 2007)
Osteoporosis (OP) is now well recognized in patients with ankylosing spondylitis (AS). Vertebral fractures that result from osteoporosis are a feature of longstanding AS. In AS, diagnosis of osteoporosis is still often a challenge. Although bone density has been measured in patients with AS, the high incidence of syndesmophyte formation and ligamentous calcification makes interpretation difficult. Alternative sites such as the neck of the femur should be used for sequential assessment of bone mineral density in AS. In this paper, pathophysiology, diagnosis and treatment method of osteoporosis and vertebral fracture in patients with AS are reviewed according to the recent studies. (From the World of Osteoporosis 2007;13:83-7)